Web Backend Development on MyGKM Application: Pengembangan Web Backend Pada Aplikasi MyGKM - Falerio Tumimomor; Sherwin R.U.A. Sompie; Sary D. E. Paturusi (Universitas Sam Ratulangi, 2026)
Abstract —The rapid advancement of information technology has encouraged the adoption of web-based information systems across various sectors, including religious institutions, to support effective and efficient data management. GMIM Kristus Manado Church has implemented an Android-based information application (MyGKM); however, administrative data management is still partially handled manually, resulting in inefficiencies. This study aims to develop a web-based back-end system for the MyGKM application to improve the efficiency and accuracy of administrative data management. The Rapid Application Development (RAD) method was employed, consisting of requirement planning, system design, implementation, and testing phases. The system was developed using ReactJS for the user interface and Firebase as the database. The results indicate that the proposed system simplifies administrative tasks related to managing worship information and church news, and all system functionalities operated as expected based on black box testing results. Keywords— Admin; Back-end; Firebase; ReactJS; Web. Abstrak —Perkembangan teknologi informasi mendorong pemanfaatan sistem informasi berbasis web pada berbagai sektor, termasuk bidang kerohanian, untuk mendukung pengelolaan data dan penyampaian informasi secara efektif dan efisien. Gereja GMIM Kristus Manado telah memiliki aplikasi informasi berbasis Android (MyGKM), namun proses pengelolaan data oleh admin masih dilakukan secara manual sehingga kurang optimal. Penelitian ini bertujuan untuk mengembangkan web back-end pada aplikasi MyGKM guna meningkatkan efisiensi dan akurasi pengelolaan data oleh admin gereja. Metode yang digunakan adalah Rapid Application Development (RAD) dengan tahapan perencanaan kebutuhan, desain, implementasi, dan pengujian. Sistem dikembangkan menggunakan ReactJS sebagai antarmuka pengguna dan Firebase sebagai basis data. Hasil penelitian menunjukkan bahwa sistem yang dibangun mampu mempercepat proses pengelolaan berita dan informasi ibadah, serta seluruh fungsi sistem berjalan dengan baik berdasarkan hasil pengujian black box. Kata kunci — Admin; Back-end; Firebase; ReactJS; Web.